2010
DOI: 10.1590/s0100-736x2010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma marginale infection in cattle from south-western Amazonia

Abstract: 249Pesq. Vet. Bras. 30(3):249-254, março 2010 RESUMO.-[Infecção por Anaplasma marginale em bovinos na Amazônia Sul Ocidental, Brasil.] O presente estudo fornece os primeiros dados epidemiológicos relativos a infecção por Anaplasma marginale em bovinos criados na Amazônia Sul Ocidental brasileira. Foi adaptado um procedimento simples para a extração de DNA a partir de coágulos sanguíneos coletados em sete microrregiões do estado de Rondônia e duas mesoregiões do estado do Acre. A técnica da reação em cadeia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(19 reference statements)
1
9
1
1
Order By: Relevance
“…This was similar to what was found by Torioni de Echaide et al (1998) in Oregon, USA, with 64% of positive animals, and lower than what was observed by Brito et al (2010) in Rondônia and Acre, Brazil, who found that 98.6% and 92.4% of the animals were positive, respectively, among animals aged between 4 and 12 months, using PCR in both studies. These higher results obtained by Brito et al (2010) may have been influenced by several factors, including age, since their study was conducted exclusively using calves. In the results from the present study, the calves also showed higher values (P < 0.01).…”
Section: Discussionsupporting
confidence: 90%
“…This was similar to what was found by Torioni de Echaide et al (1998) in Oregon, USA, with 64% of positive animals, and lower than what was observed by Brito et al (2010) in Rondônia and Acre, Brazil, who found that 98.6% and 92.4% of the animals were positive, respectively, among animals aged between 4 and 12 months, using PCR in both studies. These higher results obtained by Brito et al (2010) may have been influenced by several factors, including age, since their study was conducted exclusively using calves. In the results from the present study, the calves also showed higher values (P < 0.01).…”
Section: Discussionsupporting
confidence: 90%
“…PCR based assay for sensitive diagnosis of B. babesiosis has been attempted by many workers with high degree of sensitivity and specificity worldwide (Fahrimal et al 1992;Salem 1998;Smeenk et al 2000;Santana et al 2001;Linhares et al 2002;Silva et al 2009;Brito et al 2010;Shams et al 2013). A PCR based assay for sensitive detection of B. bigemina was originally described by Figueroa et al (1992), targeting 278 bp fragment specific of parasite DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical distribution and clinical significance of Ehrlichia/Anaplasma infections in cattle are well documented for some species (E. ruminantum, A. marginale, and A. phagocytophilum) (Brito et al, 2010;Aktas and Özübek, 2015). However, little information is available on other species (e.g., E. minasensis).…”
Section: Anaplasmataceaementioning
confidence: 99%
“…However, little information is available on other species (e.g., E. minasensis). In Brazil, only A. marginale (Brito et al, 2010) and recently Ehrlichia sp. infections have been reported in cattle (Aguiar et al, 2014).…”
Section: Anaplasmataceaementioning
confidence: 99%